HUBUNGAN KECERDASAN EMOSIONAL DENGAN TINGKAT KEPATUHAN PROTOKOL KESEHATAN REMAJA SELAMA PANDEMI COVID-19 DI SMK N 1 SIAU TIMUR - Sakendatu, Sarah; Bidjuni, Hendro Joli; Natalia, Adriani (JURNAL KEPERAWATAN, 2024)
Background: The results of the initial data survey conducted at SMK N 1 Siau Timur found that some students still did not comply with health protocols properly. Emotional condition is an internal factor that can affect a person's compliance so adolescents must have high emotional intelligence to overcome non-compliance in the application of health protocols. Objective: to investigate the relationship of emotional intelligence with the level of compliance with teen health protocols during the COVID-19 pandemic in SMK N 1 East Siau. Methods: Using a quantitative approach, cross-sectional research design, sample 186, using the TEIQue-SF questionnaire and the Health Protocol Compliance Level questionnaire, data processing was carried out through statistical analysis with the help of the SPSS program. Results: Most of adolescents have emotional intelligence in the medium category as many as 126 people (67.7%). The level of compliance with health protocols, most of the adolescents did not comply, as many as 112 people (60.2%). Conclusions: There is a relationship between emotional intelligence and the level of compliance with adolescent health protocols during the COVID-19 pandemic.